Relationship Between School Administrators’ Leadership and Teachers’ Motivation in Chonburi Area 3 under Secondary Educational Service Area Office, Chonburi and Rayong - Wongpleaw, Pratchaya; Nirundorn, Jutharat (Journal of Buddhist Education and Research (JBER), 2025)
The research aimed to (1) study the leadership level of school administrators (2) study the motivation level of teachers (3) study the relationship between the leadership of school administrators and the motivation of teachers in Chonburi 3, under the Office of the Secondary Education Area, Chonburi Rayong. The population used in the research was 285 teachers. The sample size was determined using the Krejci and Morgan table with a stratified random sampling method and then simple random sampling. The statistical values ​​used in the research data analysis were mean, standard deviation, and Pearson's correlation coefficient. The research results found that: Leadership of school administrators Overall, it is at the highest level in of motivation for teachers. and the relationship motivation was found to have a positive relationship at a moderate level.